Satisfaction and Motivation as Determinants of Teacher Performance - Rasto Rasto; Siti Yulianti Maulani (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
The goal of this research is to investigate the influence of satisfaction and motivation of teacher performance. The method of this research is explanatory survey. Data were collected by questionnaire rating scale 5 scale models. Respondent are teachers of state Vocational High School. Respondent are teachers of State Vocational High School in Cimahi. Data analysis technique using regression. The finding of this research indicated that satisfaction and motivation have a positive and significant influence on teacher performance, either partially or simultaneously. The research concluded that the teacher’s performance can be improved by improving the satisfaction and motivation.